2008
DOI: 10.4049/jimmunol.181.10.7390
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Macrophage/Epithelial Cell-Derived CCL11/Eotaxin-1 Mediates Eosinophil Recruitment and Function in Pediatric Ulcerative Colitis

Abstract: *Clinical studies have demonstrated a link between the eosinophil-selective chemokines, eotaxins (eotaxin-1/CCL11 and eotaxin-2/CCL24), eosinophils, and the inflammatory bowel diseases, Crohn's disease and ulcerative colitis (UC). However, the cellular source and individual contribution of the eotaxins to colonic eosinophilic accumulation in inflammatory bowel diseases remain unclear. In this study we demonstrate, by gene array and quantitative PCR, elevated levels of eotaxin-1 mRNA in the rectosigmoid colon o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
159
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(177 citation statements)
references
References 70 publications
17
159
1
Order By: Relevance
“…Our results demonstrate that, when colitis is induced, eosinophil accumulation to the submucosa of the cecum and midcolon occurs independently of mast cells (Figure 4). In agreement with our findings, Ahrens et al 18 identified intestinal macrophages as the primary producers of CCL11 after DSS treatment. This suggests that mast cellindependent mechanisms of eosinophil accumulation predominate during experimentally induced colitis.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results demonstrate that, when colitis is induced, eosinophil accumulation to the submucosa of the cecum and midcolon occurs independently of mast cells (Figure 4). In agreement with our findings, Ahrens et al 18 identified intestinal macrophages as the primary producers of CCL11 after DSS treatment. This suggests that mast cellindependent mechanisms of eosinophil accumulation predominate during experimentally induced colitis.…”
Section: Discussionsupporting
confidence: 94%
“…16,17 Moreover, this eosinophil recruitment was highly dependent on the activity of CCL11. 16,18 Toll-like receptors (TLR) are a family of innate immune pattern recognition receptors that recognize pathogenassociated molecular patterns. Several TLRs are expressed in the large intestine under normal physiological conditions and during inflammation.…”
mentioning
confidence: 99%
“…6 phils in the blood or colon of patients with IBD, particularly those with ulcerative colitis, is unclear. [23][24][25][26] The correlation of increased numbers of eosinophils in inflamed tissue and the ability of eosinophil-derived molecules (eg, major basic protein) to cause tissue damage has led to the supposition that these cells contribute to inflammation: a postulate supported by data from animal models of colitis. [27][28][29][30] However, the release of TGF␤ from eosinophils can promote tissue restitution.…”
Section: Discussionmentioning
confidence: 85%
“…However, the possibility that infection with helminth parasites could exaggerate disease cannot be overlooked, as for example in Citrobacter rodentium-induced enteropathy 34 and oxazolone-induced colitis. 13 Given the commonality of i) increased IL-4 in ulcerative colitis and murine oxazolonecolitis, ii) increased eosinophils in oxazolone-induced colitis 15 and some patients with ulcerative colitis, 24 and iii) the mobilization of IL-5 and eosinophils after infection with helminth parasites, 35 we hypothesized that IL-5 and eosinophils participated in the worsening of oxazoloneinduced colitis in H. diminuta-infected mice. The subsequent analyses support three conclusions: first, the exaggeration of oxazolone-induced colitis observed in H. diminuta-infected mice is inhibited by in vivo neutralization of IL-5; second, increased production of IL-5 worsens the outcome of oxazolone-induced colitis; and, third, despite a more severe disease in H. diminutaϩoxazolone Figure 7.…”
Section: Il-5 Andmentioning
confidence: 99%
“…Upregulation of eosinophil-selective chemokines has been observed in pediatric ulcerative colitis. 28 Activation of TLR4 signaling and increased expression of important immune effectors including Ifng, Il1 and Tnf were also detected in Usp18 þ /ity9 . The importance of the IL-12/IFNg axis, TNF and IL-1 in the host response to Salmonella-induced typhoid is well known in mice [29][30][31] and increased expression of these genes have been reported by us in the spleen of Salmonella-infected mice.…”
Section: Discussionmentioning
confidence: 97%